Correlation between changes of amino acid spectrum and alopecia in patients with obesity undergoing bariatric surgery: a prospective cohort study - Wang, Tingwen; Huang, Jiaqing; Sun, Xin; Zhao, Hai; Bao, Jun; Chu, Xuehui; Bian, Xiaojie (Frontiers in Nutrition, 2025)
PurposeTo investigate the association between serum amino acid changes and alopecia in patients with obesity before and after bariatric surgery, and identify risk factors for postoperative alopecia.MethodsThis prospective cohort study (ChiCTR2300074104) included patients with obesity undergoing laparoscopic sleeve gastrectomy (LSG), categorized into non-mild alopecia (NM group, n = 24) and moderate–severe alopecia (MS group, n = 43) groups. Clinical data and serum amino acid concentrations were analyzed to: (1) compare preoperative and postoperative amino acid profiles; (2) evaluate amino acid differences between groups at various timepoints and correlate with alopecia severity; (3) perform logistic regression to identify alopecia risk factors.ResultsAmong 67 patients analyzed, LSG significantly decreased serum concentrations of arginine, alanine, threonine, glutamic acid, branched-chain amino acids (valine, isoleucine, leucine), and aromatic amino acids (tyrosine, phenylalanine, tryptophan) (p < 0.05), while serine and glycine increased (p < 0.05). At 3 months postoperatively, leucine levels were higher in the MS group compared to the NM group. Spearman’s correlation analysis revealed threonine, γ-aminobutyric acid, and leucine levels were associated with alopecia severity (p < 0.05). Logistic regression identified serum leucine as an independent risk factor for postoperative alopecia (OR = 1.119, 95% CI 1.006-1.245, p = 0.038).ConclusionLSG surgery alters the serum amino acid profile in patients with obesity, and serum leucine concentration at 3 months postoperatively is an influential factor in postoperative alopecia.